Sequential finite element modelling of lightning arc plasma and composite specimen thermal-electric damage. (1st October 2019) - Millen, S.L.J.; Murphy, A.; Abdelal, G.; Catalanotti, G.
Highlights: A methodology to transfer loading boundary conditions from a lightning plasma simulation to a material damage simulation. The first time prediction of thermal-electric damage for test 'Waveform B'. Predicted specimen damage based on test electric input conditions and not assumed specimen surface loading conditions. Abstract: Highly complex phenomena such as lightning strikes require simulation methods capable of capturing many different physics. However, completing this in one simulation is not always desired or possible. In such instances there can be a need for a methodology to transfer loading boundary conditions from one simulation to the next while accounting for the characteristic form of the loading and the dissimilar domain and mesh geometries. Herein, the objective is to combine two models to enable the automatic sequential simulation of a lightning arc and a composite test specimen. The approach is developed using Finite Element models, with a Magnetohydrodynamics model representing the lightning plasma and a thermal-electric model representing the specimen. The specimen mesh and loading boundary conditions are automatically generated based on the predicted output of the preceding plasma model. The precision, run-time and flexibility of the proposed approach is demonstrated, with thermal damage predictions generated in approximately 33 h. Resulting from the integrated modelling capability is the first time prediction of damage representing the test electric boundary conditions rather than assumed specimen boundary conditions (herein using test 'Waveform B').